2017
DOI: 10.1021/acs.jpcc.7b05709
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Carbon Nanotubes Networks Grown on Silicon Nanoparticles as Li-Ion Anodes

Abstract: Using chemical vapor deposition, we grew carbon nanotubes (CNTs) on the surface of Si nanoparticles (NPs) that were coated with a thin iron shell. We studied the CNT growth mechanisms and analyzed the influence of (1) varying annealing times and (2) varying growth times. We show that an initial annealing is necessary to reduce the iron oxide shell and to start the formation of Fe NPs and their consequent coarsening. We characterize the evolution of the catalyst morphology and its influence of the morphology an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…In a previous work, we showed the growth of CNTs on the surface of silicon particles coated with a thin iron oxide, where iron oxide was first reduced (like in our case) by an annealing in reductive atmosphere (Ar/H 2 ), with subsequent dewetting of the iron surface into nanosized dots, which were the nucleation sites for CNT growth (see Figure 1 and 2 in 58 ). Although in this previous work the iron oxide layer was thin and could dewet, we (and others) have shown that direct growth on bulk ironcontaining materials such as stainless steel can grow CNTs.…”
Section: Acs Applied Nano Materialssupporting
confidence: 58%
“…In a previous work, we showed the growth of CNTs on the surface of silicon particles coated with a thin iron oxide, where iron oxide was first reduced (like in our case) by an annealing in reductive atmosphere (Ar/H 2 ), with subsequent dewetting of the iron surface into nanosized dots, which were the nucleation sites for CNT growth (see Figure 1 and 2 in 58 ). Although in this previous work the iron oxide layer was thin and could dewet, we (and others) have shown that direct growth on bulk ironcontaining materials such as stainless steel can grow CNTs.…”
Section: Acs Applied Nano Materialssupporting
confidence: 58%
“…Impressive results were achieved in previous reports where CNTs grown on the surface of Si particles for battery applications, however in these reports, CNTs were not structured in secondary particles. As a result, these batteries were only tested in low loading levels and show poor CE. In contrast, our CVD process on secondary particles reduces the BET surface area and therefore improves the CEs of the material .…”
mentioning
confidence: 94%
“…To the best of our knowledge, the Si/MWCNTs composites in ZIBs and AIBs are poorly researched. Nevertheless, several studies could be identified for LIBs, proposing approaches for Si nanoparticles (NPs) integrated into CNTs, such as covalent bonding between Si NPs and CNTs , and growth of CNTs on Si. , According to Martin et al , the presence of CNTs’ covalent bonds close to Si NPs improved the electronic pathway to the active material particles and prevented silicon destruction by improving the electrode’s mechanical stability at the nanoscale level. In comparison to the simple mixing of the two compounds, the integration resulted in greater cycling ability and higher capacity in the composite electrode .…”
Section: Introductionmentioning
confidence: 99%